2010
DOI: 10.1007/s11104-010-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of soybean roots subjected to short-term drought stress

Abstract: Drought is one of the most important constraints on the growth and productivity of many crops, including soybeans. However, as a primary sensing organ, the plant root response to drought has not been well documented at the proteomic level. In the present study, we carried out a proteome analysis in combination with physiological analyses of soybean roots subjected to severe but recoverable drought stress at the seedling stage. Drought stress resulted in the increased accumulation of reactive oxygen species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
83
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 59 publications
12
83
0
Order By: Relevance
“…The Sadenosylmethionine synthetase gene is expressed in all living cells, and its product, Sadenosyl-L-methionine, is the major methyl donor in all cells. It has been shown that the expression of S-adenosylmethionine synthetase in soybean root decreases upon exposure to drought stress (Alam et al, 2010b). Down-regulation of this enzyme under drought is consistent with the inhibition of photosynthetic activity as a general feature of abiotic stresses.…”
Section: Protein Identificationmentioning
confidence: 61%
See 2 more Smart Citations
“…The Sadenosylmethionine synthetase gene is expressed in all living cells, and its product, Sadenosyl-L-methionine, is the major methyl donor in all cells. It has been shown that the expression of S-adenosylmethionine synthetase in soybean root decreases upon exposure to drought stress (Alam et al, 2010b). Down-regulation of this enzyme under drought is consistent with the inhibition of photosynthetic activity as a general feature of abiotic stresses.…”
Section: Protein Identificationmentioning
confidence: 61%
“…Carbohydrate metabolism is likely to be most affected by drought stress after photosynthesis. Proteome analysis of soybean root under drought condition showed that two key enzymes involved in carbohydrate metabolism, UDPglucose pyrophosphorylase and 2,3-bisphosphoglycerate independent phosphoglycerate mutase, were down-regulated upon exposure to drought (Alam et al, 2010b). The levels of expression of both enzymes tended to revert to that of the control plants when watering was restored.…”
Section: Protein Identificationmentioning
confidence: 98%
See 1 more Smart Citation
“…This protein is believed to have a detoxicating capability in case of excessive concentrations of iron, ozone, NO or hydrogen peroxide (Zhao et al, 2002;Theil et al, 2006;Arosio et al, 2009); it may also be able to detoxicate the cell from tetracycline. Data accumulated so far indicate that ferritin is stimulated by dehydration and excessive moisture content (Ravet et al, 2009;Alam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After recovery, decreased proline content was observed but it remained higher for each variety when compared with the control plants of the same variety. Studies of plants under drought stress indicate proline accumulation as a protective behaviour (Alam et al, 2010;Keyvan, 2010;Yazdanpanah et al, 2011;Alam et al, 2013). Turkan et al (2005) observed higher proline content in drought tolerant plants in comparison to sensitive plants.…”
mentioning
confidence: 99%